Genetic evaluation of Jatropha backcross hybrid clones (BC4F1) for yield and oil quality - Jawahar Vishnu, M. V.; Parthiban, K. T.; Umadevi, M.; Sudhagar, R. Jude; Fernandaz, C. Cinthia; Javed, Talha; Kumar, Uttam; Alotaibi, Saqer S. (Frontiers in Genetics, 2022)
Jatropha curcas is a tropical species that has been recognized as a promising biodiesel plant. Attempts were made during 2018 - 2021 at FC&RI, Mettupalayam, to elicit information on biochemical characteristics, growth performance, variability, and association studies in biometric variables using five backcross (BC4F1) hybrid clones of Jatropha with a control variety TNMC 7. In terms of seed yield, two-hybrid clones, CJH 13 (1218.60 g) and CJH 12 (1034.40 g), outperformed the other hybrid clones. Seed oil content was higher in CJH 5. (34.19%). Seed oil content had moderate Phenotypic Coefficient of Variation (16.49%) and Genotypic Coefficient of Variation (16.39%) values, as well as high heritability (99%) and genetic advance (33.56%) as a percentage of the mean. The number of fruits per bunch (0.845 & 0.850) and the number of bunches per branch (0.771 & 0.788) had significant and positive phenotypic and genotypic correlations with seed yield, respectively. The iodine number, cetane number, and saponification value of all hybrid clones were acceptable and satisfactory and were in good compliance with Indian and international biodiesel standards.